How AI is Transforming Real Estate: Insights from the Hospitality & Multifamily Sectors - Marsella, F N U; Paul, Sanil (Transactions on Engineering and Computing Sciences, 2025)
Artificial intelligence (AI) is transforming the hospitality and multifamily real estate sectors, enhancing revenue management, customer experience, and operational efficiency. This paper examines how AI-driven technologies are reshaping these industries, highlighting their applications, benefits, and challenges. In the hospitality sector, AI optimizes revenue through dynamic pricing, enhances guest experiences with intelligent automation, and reduces operational costs via predictive maintenance. Meanwhile, in the multifamily sector, AI streamlines tenant screening, automates leasing, improves resident engagement, and integrates smart home technologies to enhance security and efficiency. AI-powered market analysis, rent optimization, and predictive maintenance further improve asset performance in both sectors. Despite its transformative potential, AI adoption presents challenges such as high initial costs, algorithmic bias in tenant screening and pricing models, and data privacy concerns. The integration of AI with emerging technologies like blockchain and IoT is also explored as a potential solution to enhance security, transparency, and efficiency in real estate operations. By analyzing real-world case studies and industry data in hospitality and multifamily sectors, this study explores best practices for AI implementation, provides a glimpse into what the future could hold for real estate with AI, and offers strategic recommendations for stakeholders looking to maximize efficiency, profitability, and long-term sustainability in an AI-driven real estate landscape.